Risk of Transient Stability Using Rotor Trajectory Index as Severity Function - Elmotaz Billa Elghali; Marayati Marsadek; Agileswari K. Ramasamy (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
This paper presents a new approach to determine the risk of transient stability. It describes the implementation of rotor trajectory index (RTI) to assess the severity of power systems when it is subjected to a three-phase fault. The (RTI) is proposed as an index used to represent severity of transient instability. Risk of transient stability for three-phase fault is calculated using a well-known risk formula. Risk of transient stability provides a quantitative measure to evaluate the potential loss of synchronism of a generator that takes into account the probability and consequences. RTI index is calculated based on the machines rotor angles obtained at each step of a time domain simulation. RTI is proposed as an index to show the severity of the three-phase fault towards transient stability since it allows a fast and accurate measurement of the degree of stability of the system facing a fault. The proposed technique is implemented on the IEEE 39-bus system.